Preliminary investigation of Laprak landslide of Gorkha district, west Nepal - Khanal, RP (Journal of Nepal Geological Society, 2008)
Owing to a heavy rainfall on 3rd July of 1999 in the northern belt of Gorkha district, a large landslide had occurred at Laprak village. Besides the high intensity of the rainfall, steep topography of the area, highly weathered and fractured rocks, soft soil covers, unfavorable orientation of the bedding plane, and day to day human activities (mainly deforestation and heavy cultivation) against the natural stability are the principle causes for the occurrence of landslides. This preliminary study was carried out in order to find out the geological setting, the causes of landslide in the area and appropriate preventative methods to be applied to mitigate the landslide problem. The studied area consists of high-grade metamorphic rocks like gneiss and garnetiferous schist with grey to white quartzite of Higher Himalaya crystalline. The gneiss in the landslide area is highly sheared, fractured and deeply weathered. The present landslide of Laprak village is active and continuously progressing towards the settlement area of the village. As the sliding process is still active and it is creating severe problems to the village even after seven years. The landslide has heavily damaged the houses and cultivated land. The inhabitants of the village are at risk from the threat of landslide every year, especially during the monsoon. Several transverse cracks up to 30 cm width are observed in the landslide area. The whole Laprak village is also situated on the old landsides. Two major landslide scarps are observed nearly 300 m upslope and 20 m downslope of the main village. There is an urgent need of sound and sustainable technical measures to be applied to prevent the landslide problem in the area. Regular monitoring of the landslide should be carried out in order to find its nature, activities and expanding behaviour. However, a more extensive study of the Laprak Landslide is required, including seismic and electrical tomography, slope stability analysis, geotechnical investigation and risk mapping in order to find landslide depth, subsurface characteristics and probable severity of the landslide. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.27